Flybys in protoplanetary discs – II. Observational signatures - Cuello, Nicolás; Louvet, Fabien; Mentiplay, Daniel; Pinte, Christophe; Price, Daniel J; Winter, Andrew J; Nealon, Rebecca; Ménard, François; Lodato, Giuseppe; Dipierro, Giovanni; Christiaens, Valentin; Montesinos, Matías; et al. (Monthly notices of the Royal Astronomical Society, 2020)
Tidal encounters in star clusters perturb discs around young protostars. In Cuello et al., we detailed the dynamical signatures of a stellar flyby in both gas and dust. Flybys produce warped discs, spirals with evolving pitch angles, increasing accretion rates, and disc truncation. Here, we present the corresponding observational signatures of these features in optical/near-infrared scattered light and (sub) millimetre continuum and CO line emission. Using representative prograde and retrograde encounters for direct comparison, we post-process hydrodynamical simulations with radiative transfer methods to generate a catalogue of multiwavelength observations. This provides a reference to identify flybys in recent near-infrared and submillimetre observations (e.g. RW Aur, AS 205, HV Tau and DO Tau, FU Ori, V2775 Ori, and Z CMa).